2019
DOI: 10.1007/s42452-019-0605-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of dopamine–sodium carboxymethyl cellulose hydrogel

Abstract: In order to prepare a biocompatible tissue adhesive and sealant with high adhesion properties, dopamine (DA) was grafted onto sodium carboxymethyl cellulose (CMC) to obtain catechol-modified CMC-DA by carbodiimide chemistry method, and then CMC-DA hydrogels was prepared by self-cross-linking. The UV-Vis spectroscopy, FTIR and 1 H NMR results showed that dopamine was successfully introduced into CMC and the degree of substitution of dopamine in the CMC-DA hydrogels was 5%, 10.5% and 15%, respectively. SEM obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…Owing to these characteristics, carboxymethylcellulose is already applied in the food, pharmaceutical, and daily-use chemical industries as an emulsifier, thickener, and a flocculating or chelating agent [45,46]. Currently, carboxymethylcellulose based materials are investigated for biomedical applications such as tissue engineering [47] and drug delivery [48] mainly in the shape of hydrogels, membranes, and nanoparticles [49]. Some of the most popular membrane manufacturing techniques include electrospinning, gradual electrostatic assembly, and phase inversion by immersion precipitation or solvent evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to these characteristics, carboxymethylcellulose is already applied in the food, pharmaceutical, and daily-use chemical industries as an emulsifier, thickener, and a flocculating or chelating agent [45,46]. Currently, carboxymethylcellulose based materials are investigated for biomedical applications such as tissue engineering [47] and drug delivery [48] mainly in the shape of hydrogels, membranes, and nanoparticles [49]. Some of the most popular membrane manufacturing techniques include electrospinning, gradual electrostatic assembly, and phase inversion by immersion precipitation or solvent evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of catechol groups in its benzene rings, the DA has obvious absorption peak at 280 mm. However, the molecular structure of CMC does not contain the same group, so there was no obvious absorption peak in the range of 225-400 nm [34]. When DA reacts with cellulose, the catechol group is grafted into the molecular chain.…”
Section: Analysis Of Cmc-damentioning
confidence: 99%
“…Some studies [32,33] have confirmed that HA nanocomposites can be prepared using CMC to simulate the natural nucleation and growth process. However, the adhesion strength of CMC is low, and it is urgent to improve the adhesion performance through modification [34]. Dopamine (DA) is a kind of amino acid, which can interact strongly with other materials through chemical and physical interaction and shows high adhesion on various materials [35].…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan inceleme neticesinde NaCMC hidrojellerinin, mükemmel şişme ve viskodinamik elastikiyet sergilediği tespit edilmiştir. Birçok araştırmacı, çoğunlukla fiziksel veya kimyasal çapraz bağlama ajanları kullanarak NaCMC temelli hidrojeller hazırlamıştır [6][7][8][9]. NaCMC temelli hidrojellerin hazırlanması için kullanılan çapraz bağlama ajanlarının birçoğunun, toksik özellikte olduğu bilinmektedir.…”
Section: Selüloz Eterleri Genellikleunclassified